The endogenous formation of economic coalitions - Carraro, Carlo (Cheltenham, UK ; Northhampton, MA, USA : E. Elgar, 2003)
Providing a substantial overview of advances in coalition theory, this book presents both theoretical developments and novel applications in the field of economics. It demonstrates the many uses of coaltion theory and its ability to address a whole host of complex economic problems.
Includes bibliographical references and index.
oif 20/02/15
Loan
Keywords: Cooperation; Trade blocs; Coalitions; Commerce